A qualitative study of nursing practitioners' experiences with COVID-19 patients dying alone in Greece - Voultsos, Polychronis; Tsompanian, Anna; Deligianni, Maria; Tsamadou, Eftychia; Tsaroucha, Alexandra K. (Frontiers in Public Health, 2022)
Background In Greece, there is still limited research on death in isolation due to COVID-19. This deserves attention because of the recent financial crisis, which profoundly impacted public health, and the high relevance of the Hippocratic tradition to the moral values of clinical practice. Methods A prospective qualitative study using in-depth interviews with 15 frontline nursing practitioners working in a COVID-19 ward or intensive care unit (ICU) was conducted from July 2021 to December 2021. Results The inability of family members to say a final goodbye before, during, or after death by performing proper mourning rituals is extremely inhuman and profoundly impacts the mental health status of patients, family members, and nursing practitioners. Patients and their family members strongly desire to see each other. Epidemiology, liability, and proper nursing performance emerged as reasons for the enforced strict visitation restrictions. Participants emphasized that visitations should be allowed on an individual basis and highlighted the need for the effective use of remote communication technology, which, however, does not substitute for in-person contact. Importantly, physicians allowed “clandestine” visits on an individual basis. Nursing practitioners had a strong empathic attitude toward both patients and their families, and a strong willingness to provide holistic care and pay respect to dead bodies. However, they also experienced moral distress. Witnessing heartbreaking scenes with patients and/or their families causes nursing practitioners to experience intense psychological distress, which affects their family life rather than nursing performance. Ultimately, there was a shift from a patient-centered care model to a population-centered care model. Furthermore, we identified a range of policy- and culture-related factors that exaggerate the negative consequences of dying alone of COVID-19. Conclusion These results reinforce the existing literature on several fronts. However, we identified some nuances related to political decisions and, most importantly, convictions that are deeply rooted in Greek culture. These findings are of great importance in planning tailored interventions to mitigate the problem of interest and have implications for other similar national contexts.